Multimedia Live: Built to Sell? - Gilinsky, Armand (Senate Hall, 2003)
The Multimedia Live (MML) case examines a company's history and evolution into a distinct niche: e-commerce Web site and technology development. MML has created a market niche in developing catalog retailers' Web sites. In this market space, MML competes against larger companies including IBM. The case focuses on Burke's important decision to fund growth via diversification slowly, using internally generated funds, or possibly more rapidly with proceeds from a sale to another business or an Initial Public Offering. Increasingly unattractive trade and stock market conditions for Internet companies have arisen during the summer of 2000. Burke has to decide whether to act quickly or wait it out until the downturn for Internet companies is over. The case is primarily intended for an undergraduate or graduate-level Entrepreneurship course to present some of the challenges associated with starting, growing and diversifying a high-tech venture in a high-velocity environment.
Keywords: business model|situation environment|change management